Children Literature as A Medium to Forter Critical Thinking: A Systematic Review on Benefit - Aisyah, Miranda Muge; Mustofa, Ali (English Department, Faculty of Humanities, Andalas University, 2023)
This paper aims to investigate children’s literature as a medium to foster critical thinking. This study used a qualitative method with purpose to know the meaning of the phenomena that happen. In this case, problem-solving discussion was applied as a method to deal with the issue. This was done by cross-checking and eclectic review from different sources. Research finding has revealed that children’s literature is a great media for ELT young learner’s overall language and literacy competence. In particular, children literature dealing with different cultures or social issues can promote intercultural understand and social justice. Children literature is beneficial to fostering critical thinking in language classroom more enjoyable. In short, the young learner begins to create new ideas, motivating them to acquire foreign language, expanding student’s awareness, and understanding another culture. They are naturally motivated by questioning and learning that occurs along with other students and guided by the teacher who always encourage them.